Examining the Marketing Displays, Cross-Promotion advertisement and Iinterstitials advertisement in PC games and its effect on attracting customers of the banking industry (Study case: Bank Melli) - Fotoheezadeh, Mahsa; Piri, Muhammad (International Journal of Business Management and Entrepreneurship, 2024)
The present research has been conducted to investigate the marketing displays, cross-promotion advertising and Iinterstitials advertising in pc games and its effect on attracting customers. The statistical population consists of gamers who are members of game groups in social networks as well as game nets of Hamedan province, the statistical sample of 384 people was calculated based on Cochran's formula. 23spss and smart pls software were used to perform statistical calculations. The validity value is calculated based on Cronbach's alpha coefficient, which the obtained coefficient (0.981) confirms the high validity of the questionnaire. According to the results of statistical tests, marketing displays has a positive and significant effect on attracting banking industry customers. Also, there is no significant relationship between cross-advertising and Iinterstitials advertising in computer games and attracting bank customers. It is suggested that the managers and officials of the banking industry pay special attention to the marketing displays in attracting new banking customers.